49th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2011
DOI: 10.2514/6.2011-917
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Exhaust Plume Effects on Sonic Boom for a 59-Degree Wing Body Model

Abstract: Reducing or eliminating the operational restrictions of supersonic aircraft over populated areas has led to extensive research at NASA. Restrictions are due to the disturbance of the sonic boom, caused by the coalescence of shock waves formed off the aircraft. Recent work has been performed to reduce the magnitude of the sonic boom N-wave generated by airplane components with focus on shock waves caused by the exhaust nozzle plume. Previous Computational Fluid Dynamics (CFD) analyses showed how the shock wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the 1x1 SWT, the experimental pressure signatures were measured at one-diameter away from the nozzle centerline, collected on the side opposite the model support strut. Data were collected at this location due to space restrictions in a small wind tunnel, and is consistent with previous experiments 9 . Experimental pressure signatures (ΔP/P) were collected at 0.1 inch (sometimes 0.05 inch) increments.…”
Section: Iiia Experimental Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In the 1x1 SWT, the experimental pressure signatures were measured at one-diameter away from the nozzle centerline, collected on the side opposite the model support strut. Data were collected at this location due to space restrictions in a small wind tunnel, and is consistent with previous experiments 9 . Experimental pressure signatures (ΔP/P) were collected at 0.1 inch (sometimes 0.05 inch) increments.…”
Section: Iiia Experimental Resultssupporting
confidence: 80%
“…The study of exhaust nozzle plume effect on sonic boom has progressed from analysis and testing of an isolated nozzle to slot nozzles 8 and engine-wing-body models 9,10 . These studies also demonstrated how the nozzle lip shock from an under-expanded nozzle plume could suppress the nozzle boat-tail expansion and reduce the strength of the trailing shock.…”
Section: Introductionmentioning
confidence: 99%
“…Tests were performed in a 4-foot by 4-foot supersonic wind tunnel with pressure measurements taken one diameter away from the nozzle. Study of exhaust nozzle plume effect on sonic boom has progressed from analysis and testing of an isolated nozzle 4,5 , to slot nozzles 6 and engine-wing-body models 7,8 . These studies demonstrated how the nozzle lip shock from an under-expanded nozzle plume could suppress the nozzle boat-tail expansion and reduce the trailing shock.…”
Section: Introductionmentioning
confidence: 99%
“…The study of exhaust nozzle plume effect on sonic boom has progressed from analysis and testing of an isolated nozzle to analysis of slot nozzles 6 and engine-wing-body models 7,8 . These studies also demonstrated how the nozzle lip shock from an under-expanded nozzle plume could suppress the nozzle boat-tail expansion and reduce the strength of the trailing shock.…”
Section: Introductionmentioning
confidence: 99%